Impact of distance on postoperative follow-up in patients of pediatric surgery: a retrospective review - Meagan E Wiebe; Anna C Shawyer (BMJ Publishing Group, 2020)
Objective Centralization of medical services in Canada has resulted in patients travelling long distances for healthcare, which may compromise their health. We hypothesized that children living farther from a children's hospital were offered and attended fewer follow-up appointments.Methods We reviewed children less than 17 years of age referred to the general surgery clinic at a tertiary children's hospital during a 2-year period who underwent surgery. Descriptive statistics were performed.Results We identified 723 patients. The majority were male (61%) with a median age of 7 years (range 18 days to16 years) and were from the major urban center (MUC) (56.3%). The median distance travelled to hospital for MUC patients was 8.9 km (range 0.9-22 km) vs 119.5 km (range 20.3-1950 km) for non-MUC patients. MUC children were offered more follow-up appointments (72.7% vs 60.8%, p<0.05). No significant differences existed in follow-up attendance rates (MUC 88.5% vs non-MUC 89.1%, p=0.84) or postoperative complications (9.8% vs 9.2%, p=0.78). There were no deaths.Conclusions Patients living farther from a hospital were offered fewer follow-up appointments, but attended an equivalent rate of follow-ups when offered one. Telemedicine and remote follow-up are underused approaches that can permit follow-up appointments while reducing associated travel time and expenses.